STABILISASI TANAH LEMPUNG DENGAN ABU TANDAN SAWIT DAN SEMEN TERHADAP TINGKAT KEPADATAN TANAH - Muthia Anggraini; Virgo Trisep Haris; Alfian Saleh (LPPM Universitas Abdurrab, 2022)
Building construction requires soil conditions that have good bearing capacity so that they can bear the load on it. Clay soils with high plasticity are soils that contain lots of clay grains. The properties of clay that need to be considered are the properties of compression, permeability, and shear strength. To increase the carrying capacity of the clay by compacting it, so that the maximum density is obtained. Mixing the original soil with palm bunch ash and cement will increase the maximum dry density value of clay soil. The purpose of this study was to determine the compaction of the soil mixed with various percentages of palm bunch ash and cement, respectively 5%, 7.5%, and 10%. The addition of palm bunch ash and cement can reduce the value of soil moisture content and increase the value of the dry density of the soil so that the soil becomes denser. The largest dry density value in a mixture of 10% palm bunch ash and cement was 1.42 g/cmÂ³, whereas the dry density value of the original soil was 1.32 g/cmÂ³. The conclusion is that there is an increase in the dry density value of the soil and a decrease in the value of the soil moisture content with the addition of palm bunch ash and cement.